2012
DOI: 10.5897/ajb11.2020
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of liquid culture methods and effect of temporary immersion bioreactor on growth and multiplication of banana (Musa, cv. Dwarf Cavendish)

Abstract: Four different liquids, as well as solid culture methods used in shoot propagation of banana were compared. Treatments studied were solid medium (A), liquid medium with immersion of plants (B), liquid medium with cotton culture support (C), liquid medium aerated by bubbling (D), and liquid medium with a temporary immersion bioreactor system (TIB) for 20 min every 1 h (E). After 4 weeks of culture, shoots in liquid medium with immersion and liquid medium aerated by bubbling showed none too little proliferation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…Ramos-Castellá et al (2014) observed a substantial increase in the multiplication rates using a liquid medium in vanilla. Similarly, Farahani and Majd (2012) in Musa spp., Arencibia et al (2013) in raspberry and Quiala et al (2012) in teak, managed to increase multiplication rates using TIS. In semisolid medium, the explants absorb the nutrients through the surface of the cut, and translocate the components by water movements from xylem to phloem.…”
Section: Shoot Numbermentioning
confidence: 96%
“…Ramos-Castellá et al (2014) observed a substantial increase in the multiplication rates using a liquid medium in vanilla. Similarly, Farahani and Majd (2012) in Musa spp., Arencibia et al (2013) in raspberry and Quiala et al (2012) in teak, managed to increase multiplication rates using TIS. In semisolid medium, the explants absorb the nutrients through the surface of the cut, and translocate the components by water movements from xylem to phloem.…”
Section: Shoot Numbermentioning
confidence: 96%
“…Protoplast-derived microcolonies were individually picked up from filter paper layer and gently transferred onto regeneration medium P containing MS medium, 2 mg L 1 IAA, 3 mg L 1 BAP, and 7.5 g L 1 agarose (pH 5.7) (Farahani and Majd 2012). The plants were cultured under 16 h photoperiod (65 µmol m 2 s 1 ) and at 27 C.…”
Section: Regenerated Plantlets From Isolated Protoplastsmentioning
confidence: 99%
“…Hyperhydricity induces morphogenic abnormalities in the developing plantlets (Haq and Dahot, 2007) and subsequently affect their survival. Attempts to control hyperhydric deformities have been largely focussed on better aeration and intermittent or partial plant submergence in the medium using temporary immersion bioreactors (Sajid and Pervaiz, 2008;Farahani and Majd, 2012). In the present study, the explants/growing shoots were supported by nylon mesh in the way that their lower part was continuously immersed in the culture medium, on the other hand, upper portion was exposed to air thus avoiding hyperhydricity of the growing shoots and also preventing sinking of the explants/growing shoots to the bottom of the culture vessel.…”
Section: Up-scaling Of Shoot Cultures Of C Borivilianum In Bioreactormentioning
confidence: 99%
“…The aeration at the rate of 0.5 L/min and agitation at 75 rpm were found opti-mal for the shoot growth in the present investigation. Lack of oxygen in the liquid media containing small explants and asphyxia and hyperhydricity of explants as a results of immersion, are the major limiting factors to their growth (Farahani and Majd, 2012). Supply of compressed air inside the bioreactor chamber for decreasing humidity significantly reduced the hyperhydricity during the bioreactor culture of apple root stock 'M9 EMLA' plantlets (Chakrabarty et al, 2003).…”
Section: Up-scaling Of Shoot Cultures Of C Borivilianum In Bioreactormentioning
confidence: 99%